Zirconium corundum refractory brick and preparation process thereof
By modifying nanoalumina, the carbon nanotube core-shell structure is grown in situ on its surface, which solves the local defects caused by nanoalumina agglomeration, and achieves the uniform distribution and performance improvement of nanoalumina in zirconium corundum bricks.
Patent Information
- Application Number
- CN202411638225.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-16
- Publication Date
- 2025-02-25
AI Technical Summary
Nanoalumina is prone to agglomeration in zirconium corundum bricks, resulting in local defects and reducing the overall performance of the bricks.
By modifying the nanoalumina, a layer of carbon nanotube core-shell structure is grown in situ on the surface, preventing direct contact between the nanoalumina particles and ensuring that they are evenly distributed in the zirconium corundum bricks.
The uniform distribution of nano-alumina is achieved, forming a smaller diffuse phase, hindering crack propagation and improving the toughness and strength of the brick body.
Smart Images

Figure CN119504242A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of zirconium corundum bricks, and in particular to a zirconium corundum refractory brick and a preparation process thereof. Background Art
[0002] Zirconia corundum bricks are abbreviated as AZS, which are mainly composed of alumina and zirconium oxide, and contain a small amount of other additives. Usually the alumina content is high, and the addition of zirconium oxide gives it special properties. For example, a common zirconium corundum brick may contain about 70% alumina and 30% zirconium oxide, and may also contain trace amounts of additives such as borax and silica sol to improve sintering performance.
[0003] Zirconia corundum bricks are mainly used in glass industry tank furnaces, such as the tank wall, blast hole, upper structure, hanging wall, chest wall and other key parts of the glass melting furnace. In the glass melting furnace, zirconium corundum bricks can withstand temperatures up to 1600℃ and the erosion of glass liquid, ensuring the normal operation of the kiln and the production quality of glass. It can also be used in high-temperature industrial fields such as steel smelting furnaces, cement rotary kilns, and non-ferrous metal smelting.
[0004] In order to improve the performance parameters of zirconium corundum bricks as much as possible, various additives to improve performance are added to zirconium corundum bricks during the preparation of zirconium corundum bricks. Among them, nanomaterials have unique size effects and surface effects. Introducing nano-scale additives into zirconium corundum bricks can improve their performance. For example, the addition of nanoparticles such as nano-alumina and nano-zirconia can form a finer dispersed phase inside the brick body, hinder the expansion of cracks, and improve the toughness and strength of the brick body. At the same time, nano-additives can also synergize with the original components of zirconium corundum bricks to improve their thermal shock resistance and erosion resistance.
[0005] For example, a Chinese patent application numbered CN201410765619.1 discloses a method for preparing zirconium corundum bricks containing chromium oxide. Using fused zirconium corundum particles and chromium oxide particles as aggregates, adding chromium oxide fine powder, chromium oxide powder, α-Al 2 O 3 Powder and white corundum fine powder are used as the matrix, a binder is added, and after mixing, molding and drying, it is placed in a nitrogen kiln and sintered at a low temperature by adjusting the oxygen partial pressure of the sintering atmosphere to obtain α-Al 2 O 3 The particle size of the powder is less than 0.044mm. If the particle size unit is converted into μm, the particle size is less than 44μm, which is already nano alumina.
[0006] However, due to its high specific surface area and surface energy, nano-alumina is prone to agglomeration. If the dispersion problem cannot be effectively solved during the production process, the agglomerated nano-alumina particles may form local defects in the zirconium corundum brick, reducing the overall performance of the brick. For example, the agglomeration may become a stress concentration point, which is more likely to crack during use, affecting the strength and durability of the brick. Summary of the invention
[0007] In view of the above problems, the present invention provides a zirconium corundum refractory brick and a preparation process. By modifying the nano-alumina, a layer of carbon nanotube core-shell structure is in situ grown on the surface of the nano-alumina. This core-shell structure can prevent direct contact between the nano-alumina particles, thereby reducing the possibility of nano-alumina agglomeration, and further making the nano-alumina evenly distributed inside the amorphous corundum refractory brick, forming a finer dispersed phase inside the brick body, hindering the expansion of cracks, and improving the toughness and strength of the brick body.
[0008] To achieve the above object, the present invention provides the following technical solutions: A zirconium corundum refractory brick, comprising, by weight: 55-65 parts of alumina powder, 25-35 parts of zircon sand, 1-5 parts of modified nano alumina powder, 2-6 parts of binder, 1-2 parts of chromium oxide, 1-3 parts of yttrium oxide, 1-4 parts of flux; The alumina powder has a particle size of 1-1.5 mm and a purity of >99%. The zircon sand contains 65% zirconium oxide and 34% silicon dioxide, and has a particle size of 0.05-2 mm. The modified nano alumina powder is nano alumina modified by in-situ grown carbon nanotubes, and a layer of carbon nanotube core-shell structure is in-situ grown on the surface of the modified nano alumina.
[0009] Among them, alumina powder and nano alumina powder are both purchased from Shandong Hengjia High Purity Aluminum Technology Co., Ltd., and zircon sand is purchased from Quanzhou Huaming Trading Co., Ltd. Zircon sand is added in grades, 1-2mm is coarse-grained zircon sand, 0.2-1mm is medium-grained zircon sand, and 0.05-0.2mm is fine-grained zircon sand. The content of zircon sand added in different levels is 35% for coarse particles, 35% for medium particles, and 30% for fine particles, respectively.
[0010] Preferably, the modification method of the modified nano alumina powder comprises the following steps: Step S1, nano-alumina dispersion, by weight, adding 10 parts of nano-alumina powder to 200 parts of deionized water, and then adding 5 parts of dispersant, using an ultrasonic disperser for ultrasonic treatment, the ultrasonic power is 400W, the frequency is 40kHz, and the ultrasonic time is 60min, so that the nano-alumina is evenly dispersed in the solution; Step S2, catalyst loading, preparing 100 parts of nickel nitrate hexahydrate solution with a concentration of 0.1 mol / L, using nickel nitrate hexahydrate as a catalyst precursor, slowly adding the nano-alumina solution dispersed in step S1 into the nickel nitrate solution, magnetically stirring at room temperature for 30 minutes at a stirring speed of 400 r / min, so that the nickel nitrate is uniformly adsorbed on the surface of the nano-alumina, rotary evaporating the mixed solution at 80° C. until crystallization is obtained to obtain nano-alumina powder loaded with nickel nitrate, placing the nano-alumina powder loaded with nickel nitrate in a muffle furnace, calcining at 400° C. for 3 hours at a heating rate of 5° C. / min, so that the nickel nitrate is decomposed into nickel oxide, which is used as a catalyst for growing carbon nanotubes; Step S3, in-situ growth of carbon nanotubes, nano-alumina powder loaded with nickel oxide is placed in the middle of a quartz tube of a chemical vapor deposition reactor, argon is introduced as a protective gas at a flow rate of 100 ml / min, the temperature is raised to 700°C, the heating rate is 10°C / min, and the temperature is kept at 700°C for 30 minutes to remove moisture and impurities in the powder, and then acetylene is introduced as a carbon source at a flow rate of 50 ml / min, while keeping the argon flow rate unchanged, and the reaction time is 2-3 hours, so that carbon nanotubes are grown in situ on the surface of the nano-alumina; Step S4, post-treatment, after the reaction in step S3 is completed, stop introducing acetylene, continue to cool naturally to room temperature under the protection of argon, take out the product, soak it in a 1 mol / L dilute hydrochloric acid solution for 2-3 hours to remove unreacted nickel oxide catalyst, then rinse it repeatedly with deionized water until it is neutral, and vacuum dry the modified nano-alumina at 80°C for 12 hours to obtain nano-alumina modified with in-situ grown carbon nanotubes.
[0011] Preferably, in step S1, the nano-alumina powder is γ-nano-alumina powder of 30-50 nm, with a purity of >99.9%, and the dispersant is PEG-200 polyethylene glycol; In the step S3, the purity of the acetylene is greater than 99.5%.
[0012] Preferably, the binder is silica sol, the silica sol contains 20%-40% silicon dioxide, less than 0.01% iron, less than 0.5% sodium, and has a viscosity of 10-20 mPa·s.
[0013] Preferably, the particle size of the silica sol particles in the silica sol is 20-70 nm.
[0014] Preferably, the flux is borax with a purity of >95%, an iron content of the borax of ≤0.005%, and a particle size of the borax of 0.15 mm.
[0015] In addition, the present invention also provides a method for preparing the above-mentioned zirconium corundum refractory brick, comprising the following steps: Step T1, mixing ingredients, adding alumina powder, zircon sand, modified nano alumina powder, binder, chromium oxide, yttrium oxide and flux into a mixer in sequence according to the mixing ratio; Step T2, mixing, the mixer is stirred at a speed of 120-180r / min for 90-120min to ensure that the raw materials are fully mixed; Step T3, molding, filling the raw materials mixed in step T2 into a mold, and molding using a friction brick press or a hydraulic press, with a molding pressure of 150-220 MPa and a holding time of 30-90 seconds, so that the brick reaches a preset shape; Step T4, drying: the formed bricks and the molds are placed in a drying furnace for drying to remove moisture. The drying temperature is 110-140°C and the drying time is 24-72 hours. Step T5: After sintering and drying, the green bricks and the molds are placed in an insulating sand box, and then placed in a high-temperature kiln for sintering. The sintering temperature is 1650-1800°C, the heating rate is 3-5°C / min, and the insulation time is 4-8 hours; Step T6, annealing, after the sintered zirconium corundum refractory bricks and the mold are taken out from the insulation sand box simultaneously, the mold is removed, and the zirconium corundum refractory bricks are placed back into the insulation sand box for insulation annealing treatment, the insulation time is 24-48 hours, and the cooling rate is 2-4°C / min.
[0016] Preferably, in step T5, when the brick blank and the mold are placed on the loading platform in the insulating sand box, the side support plates around the loading platform are synchronously moved toward the center of the loading platform to provide resistance and support to the side walls of the mold.
[0017] Preferably, in step T5, when the brick blank and the mold are placed in the insulating sand box, as the brick blank and the mold descend, the insulating sand stored at the bottom of the insulating sand box rises to wrap the brick blank and the mold.
[0018] Preferably, in step T6, as the zirconium corundum refractory bricks and the mold are lifted from the insulation sand box, the insulation sand flows back to the bottom of the insulation sand box for insulation storage, and is reserved for recycling when the zirconium corundum refractory bricks are annealed.
[0019] The beneficial effects of the present invention are: (1) The present invention modifies nano-alumina so that a layer of carbon nanotube core-shell structure grows in situ on the surface of the nano-alumina. The core-shell structure can prevent direct contact between nano-alumina particles, thereby reducing the possibility of nano-alumina agglomeration, and further making the nano-alumina evenly distributed inside the zirconium corundum refractory brick, forming a finer dispersed phase inside the brick body, hindering the expansion of cracks, and improving the toughness and strength of the brick body; (2) The present invention improves the refractoriness, high temperature strength and corrosion resistance of zirconium corundum refractory bricks by adding chromium oxide. The introduction of chromium oxide will not reduce the refractory performance of the material, but will improve the refractoriness because chromium oxide has a high melting point and can remain stable at high temperatures, thereby improving the overall refractory performance. In addition, during the firing process, chromium oxide can form a solid solution with aluminum oxide, etc. This solid solution connects particles and fine powders together like a "bridge", greatly improving the high temperature strength of the material. In addition, the solubility of chromium oxide in various slags is relatively low, so the refractory material containing chromium oxide has good resistance to corrosion by steel slag, non-ferrous smelting slag, etc. The liquid phase viscosity generated by the reaction between chromium oxide and slag is relatively large, which can prevent the slag from penetrating into the interior of the brick along the capillary pores, thereby avoiding the formation of a metamorphic layer and structural peeling. (3) The present invention adds yttrium oxide, which has the characteristic of a high melting point. Its addition can improve the overall refractory properties of zirconium corundum refractory bricks. Yttrium oxide can improve the softening properties of zirconium corundum bricks when bearing loads. Under the action of high temperature and pressure, the brick body is not easy to deform and maintains good strength and stability. The addition of yttrium oxide can enhance the resistance of the brick body to these corrosive media. It can react with the corrosive media to form a stable protective film to prevent further erosion. Yttrium oxide can improve the thermal shock resistance of zirconium corundum bricks. In the case of rapid temperature changes, , the brick is not easy to crack and peel off, because yttrium oxide can adjust the thermal expansion coefficient of the brick and reduce the generation of thermal stress. At the same time, it can also enhance the toughness of the brick and improve its ability to resist thermal shock. Yttrium oxide can be used as a nucleating agent to promote the growth and refinement of crystals in zircon corundum bricks. The refined grains can improve the strength and hardness of the brick, and also improve its density and uniformity. Yttrium oxide can form stable compounds at the grain boundaries of zircon corundum bricks and enhance the bonding force of the grain boundaries, which helps to improve the overall strength and toughness of the brick and prevent the cracks at the grain boundaries from expanding; (4) The present invention uses an insulating sand box to insulate the brick blank and the mold during the sintering process of zirconium corundum refractory bricks. The insulating sand box can reduce heat loss and maintain the temperature in the kiln stable, which helps to ensure that the brick blank is in a suitable temperature environment throughout the sintering process, so that the chemical reaction inside the brick body can be fully carried out, thereby improving the quality and performance of the brick. In addition, zirconium corundum bricks may deform due to thermal stress and other reasons during high-temperature sintering. The insulating sand box can provide certain support and constraints to reduce the deformation of the brick blank during the sintering process. The sand in the sand box can evenly transmit pressure so that the forces on the brick blank in all directions are relatively balanced, thereby reducing the risk of deformation. In particular, for some zirconium corundum bricks with complex shapes or large sizes, the role of the insulating sand box is more obvious. In addition, the insulating sand box can adjust the sintering atmosphere to a certain extent. The sand can absorb and release some gases, thereby affecting the atmosphere composition around the brick blank. This is very important for some zirconium corundum bricks that require specific atmosphere conditions to obtain good performance. (5) The present invention adjusts the structure of the insulating sand box so that the insulating sand inside the insulating sand box will automatically rise from the bottom of the insulating sand box when the brick blank and the mold are placed and sink into the insulating sand box to wrap the mold and the brick blank. At the same time, the insulating sand is always inside the insulating sand box, and there is no need to manually fill the insulating sand, which simplifies the operation and improves the work efficiency. After the mold and the formed zirconium corundum refractory bricks are taken out of the insulating sand box, the insulating sand will automatically return to the bottom of the insulating sand box for storage, thereby isolating and heat-insulating, and is used for the subsequent annealing treatment of the zirconium corundum refractory bricks. During the whole process, there is no need to manually fill and store the insulating sand. (6) The present invention adjusts the structure of the insulating sand box so that after the mold and the brick blank are placed in the insulating sand box, the side support plates arranged around the mold will move synchronously toward the center of the mold, so that the side support plates can synchronously support the side walls of the mold, thereby avoiding the situation where a single group of opposite sides of the mold completes support contact with the corresponding side support plates first due to the successive movement of the side support plates, causing uneven force on the mold. The positioning support force on the mold is distributed more evenly, reducing the stress concentration damage caused by uneven force on the mold during the sintering of the brick blank.
[0020] In summary, the present invention has the advantages of high quality, high forming rate, stable internal stress distribution, high temperature resistance, corrosion resistance, etc. of over-formed zirconium corundum refractory bricks, and is particularly suitable for the technical field of forming zirconium corundum refractory bricks. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a schematic diagram of the process for preparing zirconium corundum refractory bricks of the present invention; Figure 2 The figure is a schematic flow chart of the modification method of the modified nano-alumina powder of the present invention; Figure 3 It is a schematic diagram of the three-dimensional structure of the thermal insulation sand box of the present invention; Figure 4 The three-dimensional structure of the bracket of the present invention is shown in FIG. Figure 1 ; Figure 5 It is a schematic diagram of the three-dimensional structure of the mold of the present invention; Figure 6 The three-dimensional structure of the bracket of the present invention is shown in FIG. Figure 2 ; Figure 7 It is a schematic diagram of the three-dimensional structure of the side support plate of the present invention; Figure 8 It is a schematic diagram of the top view structure of the bracket of the present invention; Fig. 9 It is a schematic diagram of the local structure of the bracket of the present invention; Fig.10 It is a schematic diagram of the three-dimensional structure of the turntable of the present invention; Fig.11 It is a schematic diagram of the state of the mold of the present invention being output from the heat-insulating sand box; Fig.12 It is a schematic diagram of the heat preservation state of the mold of the present invention in the heat preservation sand box; Fig.13 This is a schematic diagram of the three-dimensional structure of the bidirectional screw shaft of the present invention; Fig.14 This is a schematic diagram of the three-dimensional structure of the thermal insulation box; Fig.15 This is a schematic diagram of the three-dimensional structure of the top sand plate of the present invention; Fig.16 It is a schematic diagram of the fracture cross-sectional structure of the thermal insulation sand box of the present invention.
[0022] In the figure: mold 100, brick 200, insulation box 1, sand bin 11, insulation bin 12, sand channel 13, top sand plate 14, partition 141, loading platform 2, bracket 3, bottom plate 31, slide 311, lifting mechanism 4, bidirectional screw shaft 41, positive thread 411, negative thread 412, positive nut 42, reverse nut 43, connecting rod 44, hand wheel 45, limit support mechanism 5, side support plate 51, guide column 511, cover plate 512, slider 513, turntable 52, teeth 521, waist groove 522, gear 53, rotating shaft 54, rotating wheel 55.
[0023] Specific embodiment The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] In the description of the present invention, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present invention.
[0025] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.
[0026] Example: A zirconium corundum refractory brick, comprising, by weight: 55-65 parts of alumina powder, 25-35 parts of zircon sand, 1-5 parts of modified nano alumina powder, 2-6 parts of binder, 1-2 parts of chromium oxide, 1-3 parts of yttrium oxide, 1-4 parts of flux; The alumina powder has a particle size of 1-1.5 mm and a purity of >99%. The zircon sand contains 65% zirconium oxide and 34% silicon dioxide, and has a particle size of 0.05-2 mm. The modified nano-alumina powder is nano-alumina modified by in-situ growth of carbon nanotubes, and a layer of carbon nanotube core-shell structure is in-situ grown on the surface of the modified nano-alumina. The binder is silica sol, the content of silicon dioxide in the silica sol is 20%-40%, the iron content is less than 0.01%, the sodium content is less than 0.5%, and the viscosity of the silica sol is 10-20mPa·s; the particle size of the silica sol particles in the silica sol is 20-70nm, and the flux is borax with a purity of >95%, the iron content in the borax is ≤0.005%, and the particle size of the borax is 0.15mm.
[0027] The main chemical reaction of producing zirconium corundum refractory bricks with zirconium silicate and alumina is relatively complex. The general reaction process and related chemical reaction formula are as follows: 1. Decomposition reaction of zirconium silicate: Under high temperature conditions, zirconium silicate will decompose to produce zirconium oxide and silicon dioxide. The chemical reaction formula is: ZrSiSO 4 →ZrO 2 +SiO 2.
[0028] 2. Reaction of alumina and silica: The generated silicon dioxide will react with aluminum oxide to form mullite and other substances. The chemical reaction formula is: 3Al 2 O 3 +2SiO 2 →3Al 2 O 3 ·2SiO 2 .
[0029] 3. Reaction of zirconium oxide and aluminum oxide: Zirconia and alumina will interact at high temperatures to form complex structures such as the eutectoid of corundum and baddeleyite. This is the main component of zirconium corundum refractory bricks. However, the reaction process is relatively complicated and there is no simple single chemical reaction formula to accurately describe it. However, it can be understood that zirconium oxide and alumina fuse and crystallize at high temperatures to form a substance with specific structure and properties.
[0030] like Figure 2 As shown, in addition, the present invention also specifically provides a method for modifying nano-alumina in situ, and the modification method of the modified nano-alumina powder comprises the following steps: Step S1, nano-alumina dispersion, by weight, adding 10 parts of nano-alumina powder to 200 parts of deionized water, and then adding 5 parts of dispersant, using an ultrasonic disperser for ultrasonic treatment, the ultrasonic power is 400W, the frequency is 40kHz, and the ultrasonic time is 60min, so that the nano-alumina is evenly dispersed in the solution, the nano-alumina powder is 30-50nm γ-nano-alumina powder, the purity is> 99.9%, and the dispersant is PEG-200 polyethylene glycol; Step S2, catalyst loading, preparing 100 parts of nickel nitrate hexahydrate solution with a concentration of 0.1 mol / L, slowly adding the nano-alumina solution dispersed in step S1 into the nickel nitrate solution, magnetically stirring at room temperature for 30 minutes at a stirring speed of 400 r / min, so that the nickel nitrate is uniformly adsorbed on the surface of the nano-alumina, rotary evaporating the mixed solution at 80° C. until crystallization, obtaining nano-alumina powder loaded with nickel nitrate, placing the nano-alumina powder loaded with nickel nitrate in a muffle furnace, calcining at 400° C. for 3 hours at a heating rate of 5° C. / min, so that the nickel nitrate is decomposed into nickel oxide, which is used as a catalyst for growing carbon nanotubes; Step S3, in-situ growth of carbon nanotubes, nano-alumina powder loaded with nickel oxide is placed in the middle of a quartz tube of a chemical vapor deposition reactor, argon is introduced as a protective gas at a flow rate of 100 ml / min, the temperature is raised to 700°C, the heating rate is 10°C / min, and the temperature is kept at 700°C for 30 minutes to remove moisture and impurities in the powder, and then acetylene is introduced as a carbon source, wherein the acetylene purity is greater than 99.5%, the acetylene flow rate is 50 ml / min, and the argon flow rate is kept unchanged. The reaction time is 2-3 hours, so that carbon nanotubes are grown in situ on the surface of the nano-alumina; Step S4, post-treatment, after the reaction in step S3 is completed, stop introducing acetylene, continue to cool naturally to room temperature under the protection of argon, take out the product, soak it in a 1 mol / L dilute hydrochloric acid solution for 2-3 hours to remove unreacted nickel oxide catalyst, then rinse it repeatedly with deionized water until it is neutral, and vacuum dry the modified nano-alumina at 80°C for 12 hours to obtain nano-alumina modified with in-situ grown carbon nanotubes.
[0031] like Figure 1 As shown, in addition, the present invention also provides a method for preparing the above-mentioned zirconium corundum refractory brick, comprising the following steps: Step T1, mixing ingredients, adding alumina powder, zircon sand, modified nano alumina powder, binder, chromium oxide, yttrium oxide and flux into a mixer in sequence according to the mixing ratio; Step T2, mixing, the mixer is stirred at a speed of 120-180r / min for 90-120min to ensure that the raw materials are fully mixed; Step T3, molding, filling the raw materials mixed in step T2 into a mold, and molding using a friction brick press or a hydraulic press, with a molding pressure of 150-220 MPa and a holding time of 30-90 seconds, so that the brick reaches a preset shape; Step T4, drying: the formed bricks and the molds are placed in a drying furnace for drying to remove moisture. The drying temperature is 110-140°C and the drying time is 24-72 hours. Step T5: After sintering and drying, the green bricks and the molds are placed in an insulating sand box, and then placed in a high-temperature kiln for sintering. The sintering temperature is 1650-1800°C, the heating rate is 3-5°C / min, and the insulation time is 4-8 hours; Step T6, annealing, after the sintered zirconium corundum refractory bricks and the mold are taken out from the insulation sand box simultaneously, the mold is removed, and the zirconium corundum refractory bricks are placed back into the insulation sand box for insulation annealing treatment, the insulation time is 24-48 hours, and the cooling rate is 2-4°C / min.
[0032] Among them, in the step T5, when the brick blank and the mold are placed on the loading platform in the thermal insulation sand box, the side support plates around the loading platform are synchronously moved toward the center of the loading platform to support the side wall of the mold.
[0033] Furthermore, in the step T5, when the brick blank and the mold are placed in the thermal insulation sand box, as the brick blank and the mold descend, the thermal insulation sand stored at the bottom of the thermal insulation sand box rises and wraps the brick blank and the mold.
[0034] In step T6, as the zirconium corundum refractory bricks and the mold are lifted from the insulation sand box, the insulation sand flows back to the bottom of the insulation sand box for insulation storage, and is kept for recycling when the zirconium corundum refractory bricks are annealed.
[0035] like Figures 3 to 16 As shown, it is specifically described that the thermal insulation sand box includes a thermal insulation box 1, a loading platform 2 and a bracket 3, wherein the thermal insulation box 1 is a square pier structure, the bottom of the thermal insulation box 1 is a square sand bin 11, the sand bin 11 gradually closes upward to form a thermal insulation bin 12, the thermal insulation bin 12 and the sand bin 11 are connected through a sand channel 13, and a lifting and moving top sand plate 14 is provided in the sand bin 11, the thermal insulation sand is filled in the sand bin 11 and the sand channel 13 above the top sand plate 14, when the top sand plate 14 is lifted, the thermal insulation sand enters the thermal insulation bin 12 through the sand channel 13, and when the top sand plate 14 is lowered, the thermal insulation sand flows back from the thermal insulation bin 12 to the sand bin 11 on the contrary; In addition, a square frame-shaped protective plate 142 is provided on the top sand plate 14, and the corresponding inner plate 10 correspondingly sleeved and matched with the protective plate 142 is provided in the heat preservation box 1. The protective plate 142 and the inner plate 10 are matched to prevent the heat preservation sand from entering the space where the lifting mechanism 4 is installed; The loading platform 2 is lifted and arranged in the insulation box 1. The loading platform 2 is horizontally arranged, and the lifting range of the loading platform 2 is within the insulation bin 12. A lifting mechanism 4 is arranged below the loading platform 2. The lifting mechanism 4 drives the loading platform 2 to lift and lower, and also drives the top sand plate 14 to lift and lower synchronously. The lifting and lowering of the loading platform 2 and the top sand plate 14 are just set in opposite directions, and the four sides of the loading platform 2 just collide with the side walls of the insulation bin 12, and the four sides of the top sand plate 14 just collide with the side walls of the sand bin 11.
[0036] Specifically, the structure of the lifting mechanism 4 includes a bidirectional screw shaft 41, a forward nut 42, a reverse nut 43, a connecting rod 44 and a hand wheel 45. The bidirectional screw 41 is horizontally rotatably arranged on the incubator 1. The axial ends of the bidirectional screw 41 are respectively provided with a spirally arranged positive thread 411 and a reverse thread 412. The forward nut 42 is arranged at the positive thread 411, and the reverse nut 42 is arranged at the reverse thread 412. When the bidirectional screw shaft 41 rotates, the forward nut 41 and the reverse nut 42 move toward or away from each other on the bidirectional screw shaft 41, and the forward nut 41 and the reverse nut 42 move toward or away from each other on the bidirectional screw shaft 41. The forward nut 41 and the reverse nut 42 are respectively hinged to the lower end of the loading platform 2 and the upper end of the top sand plate 14 through the connecting rod 44. When the forward nut 41 and the reverse nut 42 move toward each other, the angle between the connecting rods 44 becomes smaller, so that the loading platform 2 is lifted and the top sand plate 14 is lowered synchronously. Conversely, when the forward nut 41 and the reverse nut 42 move in opposite directions, the angle between the connecting rods 44 becomes larger, so that the loading platform 2 is lowered and the top sand plate 14 is raised synchronously. The hand wheel 45 is installed on the bidirectional screw shaft 41, and is used to drive the bidirectional screw shaft 41 to rotate.
[0037] The material loading platform 2 is provided with a bracket 3, which is arranged in a square frame shape and moves synchronously with the material loading platform 2. The mold 100 and the brick 200 are placed in the bracket 3. The bracket 3 is provided with a limit support mechanism 5 for supporting the mold 100 and the brick 200. The limit support mechanism 5 includes a side support plate 51 , a turntable 52, a gear 53, a rotating shaft 54 and a rotating wheel 55. The side support plates 51 are provided with four groups, which are arranged around the bracket 3, and the side support plates 51 are all slidably adjusted toward the center of the bracket 3. The bottom plate 31 of the bracket 3 is hollow inside, and a slide groove 311 is provided on the bottom plate 31 for the side support plates 51 to slide. A slider 513 corresponding to the slide groove 311 is provided at the lower part of the side support plate 51. The turntable 52 is rotatably installed in the hollow inner cavity of the bottom plate 31. A section of teeth 521 is provided on the circumference of the turntable 52, and four groups of waist-shaped grooves 522 are evenly distributed on the turntable 52 around its central axis. The waist-shaped grooves 522 are connected with the guide columns 51 provided at the lower end of the side support plates 51. 11 are arranged in a one-to-one corresponding manner. When the turntable 52 rotates, the waist-shaped groove 522 cooperates with the guide column 511 to drive the four groups of side support plates 51 to close or open to support and limit the mold 100 and the brick 200. A gear 53 is arranged next to the position where the teeth 521 are arranged on the turntable 52. The gear 53 is meshed with the teeth 521. The rotating shaft 54 is installed corresponding to the gear 53. The gear 53 is located at the bottom of the rotating shaft 54, and the rotating wheel 55 is located at the top of the rotating shaft 54. By rotating the rotating wheel 55, the gear 53 can be driven to rotate through the rotating shaft 54. The gear 53 rotates, and the turntable 52 rotates through the cooperation of the teeth 521. The turntable 52 rotates, and then the side support plates 51 are slidably adjusted.
[0038] Furthermore, a covering plate 512 for covering the chute 311 is provided on the side support plate 51 to prevent the chute 311 from being exposed and causing the insulation sand to enter.
[0039] It should be noted that the bracket 3 and the loading platform 2 are separately arranged, and a lifting ring 32 is arranged on the top of the bracket 3. When the mold 100 and the brick 200 are placed on the loading platform 2, the mold 100 and the brick 200 are first placed in the bracket 3, and then the bracket 3 is lifted to transfer the bracket 3 to the insulation box 1.
[0040] It is further explained that before the bracket 3 loaded with the mold 100 and the brick 200 is transferred into the heat preservation box 1 , the bracket 3 will resist and support the mold 100 through the above-mentioned limiting support mechanism 5 .
[0041] It is further explained that after the bracket 3 transfers the mold 100 and the brick 200 to the loading platform 2 in the insulation box 1, the loading platform 2 is lowered, so that the mold 100 and the brick 200 sink into the insulation box 1. At the same time, the top sand plate 14 rises, so that the insulation sand in the sand bin 11 is output and wrapped around the periphery of the bracket 3.
[0042] In addition, as a preference, a swingable partition 141 is provided at the position where the sand channel 13 is connected to the insulation bin 12 , and the partition 141 is used to block the heat exchange between the insulation sand and the outside air after the insulation sand returns to the sand bin 11 .
[0043] Specifically, when the loading platform 2 descends, the mold 100 and the brick 200 sink into the insulation box 1, the top sand plate 14 is lifted, and the insulation sand in the sand bin 11 is output, pushing the partition 141 to one side of the bracket 3 to tilt, and the insulation sand enters the loading platform 2 to wrap the mold 100. When the mold 100 is output, the loading platform 2 rises, the top sand plate 14 descends, and the insulation sand on the loading platform 2 flows back into the sand bin 11 again.
[0044] Embodiment 1-6: The contents of the components in Examples 1-6 are shown in Table 1: Table 1 Comparative Examples 1-6: The contents of the components in Comparative Examples 1-6 are shown in Table 2: Table 2 The performance of the zirconium corundum refractory bricks prepared in the above embodiments and comparative embodiments was tested respectively, and the results are shown in Table 3.
[0045] Among them, the test methods for apparent porosity and bulk density are: GB / T2997-2015 "Test methods for bulk density, apparent porosity and true porosity of dense shaped refractory products". The room temperature compressive strength is determined by referring to the determination method in GB / T5072-2008 "Test method for room temperature compressive strength of refractory materials"; the high temperature flexural strength of 1400°C×0.5h is determined by referring to the determination method in GB / T3002-2017 "Test method for high temperature flexural strength of refractory materials". The glass phase seepage and resistance to glass liquid erosion are tested according to JC / T805 and JC / T806 standards.
[0046] Table 3 Performance test results From the above, it can be seen that by comparing comparative examples 1-6 with comparative examples 1-6, the zirconium corundum refractory bricks prepared by the present invention improve the volume density of the zirconium corundum refractory bricks by adding modified nano alumina powder, and the compressive strength and high-temperature flexural strength are also better than those of the comparative examples, and the glass corrosion resistance is even better.
[0047] In addition, through the comparison between Examples 2, 3, and 5 and Comparative Examples 2, 3, and 5, it can be seen that the thermal insulation sand box of the present invention allows the chemical reaction inside the brick body to proceed fully, thereby further improving the volume density, compressive strength, high-temperature flexural strength, and glass corrosion resistance of the zirconium corundum refractory bricks.
[0048] Furthermore, by comparing Example 4 with Comparative Example 4, it can be seen that the modified nano alumina powder in the zirconium corundum refractory brick of the present invention forms a finer dispersed phase inside the brick body, hindering the expansion of cracks and playing a decisive role in the toughness and strength of the zirconium corundum refractory brick.
[0049] By comparing Example 1 with Comparative Example 1, and Example 6 with Comparative Example 6, it can be seen that when the content of modified alumina powder in the zirconium corundum refractory brick of the present invention is lower than a certain amount, it cannot effectively prevent the direct contact between the nano alumina particles, and the nano alumina agglomerates inside the zirconium corundum refractory brick, which will still cause the zirconium corundum refractory brick to have a high volume density, and reduce the compressive strength, high-temperature flexural strength and glass corrosion resistance. When the content of modified alumina powder is higher than a certain amount, the microstructure and chemical composition of the brick body will be changed at high temperature, destroying the original stability of the brick body, causing the zirconium corundum refractory brick to have a high volume density, and reduce the compressive strength, high-temperature flexural strength and glass corrosion resistance.
[0050] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A zirconium corundum refractory brick, characterized in that: In parts by weight: 55-65 parts of alumina powder, 25-35 parts of zircon sand, 1-5 parts of modified nano alumina powder, 2-6 parts of binder, 1-2 parts of chromium oxide, 1-3 parts of yttrium oxide, 1-4 parts of flux; The alumina powder has a particle size of 1-1.5 mm and a purity of >99%. The zircon sand contains 65% zirconium oxide and 34% silicon dioxide, and has a particle size of 0.05-2 mm. The modified nano alumina powder is nano alumina modified by in-situ grown carbon nanotubes, and a layer of carbon nanotube core-shell structure is in-situ grown on the surface of the modified nano alumina.
2. The zirconium corundum refractory brick according to claim 1, characterized in that: The modification method of the modified nano alumina powder comprises the following steps: Step S1, nano-alumina dispersion, by weight, adding 10 parts of nano-alumina powder to 200 parts of deionized water, and then adding 5 parts of dispersant, using an ultrasonic disperser for ultrasonic treatment, the ultrasonic power is 400W, the frequency is 40kHz, and the ultrasonic time is 60min, so that the nano-alumina is evenly dispersed in the solution; Step S2, catalyst loading, preparing 100 parts of nickel nitrate hexahydrate solution with a concentration of 0.1 mol / L, slowly adding the nano-alumina solution dispersed in step S1 into the nickel nitrate solution, magnetically stirring at room temperature for 30 minutes at a stirring speed of 400 r / min, so that the nickel nitrate is uniformly adsorbed on the surface of the nano-alumina, rotary evaporating the mixed solution at 80° C. until crystallization, obtaining nano-alumina powder loaded with nickel nitrate, placing the nano-alumina powder loaded with nickel nitrate in a muffle furnace, calcining at 400° C. for 3 hours at a heating rate of 5° C. / min, so that the nickel nitrate is decomposed into nickel oxide, which is used as a catalyst for growing carbon nanotubes; Step S3, in-situ growth of carbon nanotubes, nano-alumina powder loaded with nickel oxide is placed in the middle of a quartz tube of a chemical vapor deposition reactor, argon is introduced as a protective gas at a flow rate of 100 ml / min, the temperature is raised to 700°C, the heating rate is 10°C / min, and the temperature is kept at 700°C for 30 minutes to remove moisture and impurities in the powder, and then acetylene is introduced as a carbon source at a flow rate of 50 ml / min, while keeping the argon flow rate unchanged, and the reaction time is 2-3 hours, so that carbon nanotubes are grown in situ on the surface of the nano-alumina; Step S4, post-treatment, after the reaction in step S3 is completed, stop introducing acetylene, continue to cool naturally to room temperature under the protection of argon, take out the product, soak it in a 1 mol / L dilute hydrochloric acid solution for 2-3 hours to remove unreacted nickel oxide catalyst, then rinse it repeatedly with deionized water until it is neutral, and vacuum dry the modified nano-alumina at 80°C for 12 hours to obtain nano-alumina modified with in-situ grown carbon nanotubes.
3. The zirconium corundum refractory brick according to claim 2, characterized in that: In the step S1, the nano-alumina powder is 30-50 nm γ-nano-alumina powder with a purity of >99.9%, and the dispersant is PEG-200 polyethylene glycol; In the step S3, the purity of the acetylene is greater than 99.5%.
4. The zirconium corundum refractory brick according to claim 1, characterized in that: The binder is silica sol, in which the content of silicon dioxide is 20%-40%, the content of iron is less than 0.01%, the content of sodium is less than 0.5%, and the viscosity of the silica sol is 10-20 mPa·s.
5. The zirconium corundum refractory brick according to claim 4, characterized in that: The particle size of the silica sol particles in the silica sol is 20-70 nm.
6. The zirconium corundum refractory brick according to claim 1, characterized in that: The flux is borax with a purity of more than 95%, an iron content of the borax of less than or equal to 0.005%, and a particle size of the borax of 0.15 mm.
7. A method for preparing the zirconium corundum refractory brick according to any one of claims 1 to 6, characterized in that: The following steps are involved: Step T1, mixing ingredients, adding alumina powder, zircon sand, modified nano alumina powder, binder, chromium oxide, yttrium oxide and flux into a mixer in sequence according to the mixing ratio; Step T2, mixing, the mixer is stirred at a speed of 120-180r / min for 90-120min to ensure that the raw materials are fully mixed; Step T3, molding, filling the raw materials mixed in step T2 into a mold, and molding using a friction brick press or a hydraulic press, with a molding pressure of 150-220 MPa and a holding time of 30-90 seconds, so that the brick reaches a preset shape; Step T4, drying: the formed bricks and the molds are placed in a drying furnace for drying to remove moisture. The drying temperature is 110-140°C and the drying time is 24-72 hours. Step T5: After sintering and drying, the green bricks and the molds are placed in an insulating sand box, and then placed in a high-temperature kiln for sintering. The sintering temperature is 1650-1800°C, the heating rate is 3-5°C / min, and the insulation time is 4-8 hours; Step T6, annealing, after the sintered zirconium corundum refractory bricks and the mold are taken out from the insulation sand box simultaneously, the mold is removed, and the zirconium corundum refractory bricks are placed back into the insulation sand box for insulation annealing treatment, the insulation time is 24-48 hours, and the cooling rate is 2-4°C / min.
8. The method according to claim 7, characterized in that: In the step T5, when the brick blank and the mold are placed on the loading platform in the thermal insulation sand box, the side support plates around the loading platform are synchronously moved toward the center of the loading platform to support the side wall of the mold.
9. The method according to claim 7, characterized in that: In the step T5, when the brick blank and the mold are placed in the thermal insulation sand box, as the brick blank and the mold descend, the thermal insulation sand stored at the bottom of the thermal insulation sand box rises and wraps the brick blank and the mold.
10. The method according to claim 7, characterized in that: In the step T6, as the zirconium corundum refractory bricks and the mold are lifted from the insulation sand box, the insulation sand flows back to the bottom of the insulation sand box for insulation storage, and is reserved for recycling when the zirconium corundum refractory bricks are annealed.
Citation Information
Patent Citations
A kind of preparation method of zirconium corundum brick containing chromium oxide
CN104446564B
Chromium zirconium corundum aggregate, mixed active powder, chromium zirconium corundum composite material, and preparation method thereof
CN106187125A
Sintering process for preventing large-block sintered NdFeB from being cracked
CN107195413A
Al2O3-Cr2O3-ZrO2 brick for hazardous waste incinerator and preparation method of Al2O3-Cr2O3-ZrO2 brick
CN109970437A
Preparation method of low-exudation fused zirconia corundum brick added with yttrium oxide
CN112979292A
Cited By
High-strength compact fire-resistant high-chromium brick and application thereof
CN120309371A